Experimental analysis and preliminary model of non-conventional lip seals. (March 2023) - Raparelli, Terenziano; Mazza, Luigi; Trivella, Andrea
Abstract: The paper describes the tests carried out to determine the applicability of a simple means for reducing friction force in linear pneumatic actuators. The idea is based on the use of commercial lip seals mounted in the direction opposite to that used in conventional systems. Two different non-conventional installations were tested using commercial spring-energized seals consisting of two different materials: virgin PTFE and graphite-filled PTFE. Tests assessed the effect of bore manufacturing tolerances with nominal bore diameters of 50.0 mm and 50.2 mm. Performance was evaluated in terms of leakage flow rate and friction force, comparing the proposed installation with conventionally mounted seals. Friction coefficient and stiffness of the two seal materials were measured on a seal segment mounted on a pin-on-disk tribometer featuring a special pin design. Tests were carried out by loading the seal segment against a portion of the cylinder barrel in reciprocating motion. Stiffness and friction coefficient measurements served as the basis for developing a preliminary lumped parameter model of the lip seal which was used to analyze lip deflections, exchanged forces and leakage flow rate between seal and barrel. Highlights: Non-conventionally mounted lip seals. Leakage flow rate and friction force versus bore diameter and supply pressure, were measured. Tribometer with a purpose-built seal carrier pin was used to measure seal friction coefficient and the elastic stiffness. Simplified lumped parameter model of the seal: contact forces and leakage flow rate were determined.